CILILIN AS A PARAGLIDING SPORT TOURISM DESTINATION IN WEST BANDUNG REGENCY - Febrian Sonjaya; Irena Novarlia; Dally Nur Arif (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The potential for paragliding sport tourism at Bukit Gantole Cililin, West Bandung Regency, is very promising because it offers a combination of extreme sports and natural beauty. However, if this spot is to become a desirable tourist destination, serious efforts from various stakeholders are required. The purpose of this study is to determine the efforts needed to enhance the potential of Bukit Gantole Cililin so that it can develop into a paragliding sport tourism destination in West Bandung Regency. The research method used is a qualitative descriptive method. The research techniques include data collection through observation, interviews, documentation, and literature study. Based on observations and interviews, it has been shown that visitor numbers to this tourist site have continued to decline due to suboptimal management, poorly maintained and incomplete facilities, and the lack of synergy between tourism managers and the surrounding community. Therefore, this tourist site requires greater attention from various related parties. Based on field data collection, efforts to increase the potential of paragliding sport tourism at Bukit Gantole Cililin can be carried out through several measures, namely improving accessibility, facilities, transportation modes, activities, information, as well as the involvement of the government, local communities, and private sector so that Bukit Gantole tourism in West Bandung Regency can be revitalized.